Apoptosis : physiology and pathology - Reed, John C., 1958-; Green, Douglas R. (Cambridge : Cambridge University Press, 2011)
'Apoptosis, or cell death, can be pathological, a sign of disease and damage, or physiological, a process essential for normal health. This pathological dysregulation of cell death can be characterized by either too much loss of essential cells in the heart, brain, and other tissues with little regenerative capacity or by too little cell turnover in self-renewing tissues, giving rise to cancer and other maladies. This is a process of fundamental importance for development and normal health, which is altered in many disease conditions. This book, with contributions from experts in the field, provides a timely compilation of reviews of mechanisms of apoptosis. The book is organized into three convenient sections. The first section explores the different processes of cell death and how they relate to one another. The second section focuses on organ-specific apoptosis-related diseases. The third section explores cell death in non-mammalian organisms, such as plants. This comprehensive text is a must-read for all researchers and scholars interested in apoptosis'--Provided by publisher.
18. Cell death in the olfactory system Pawel Kermer; 19. Apoptosis regulation of the endocrine pancreas and pathophysiology of diabetes Nika N. Danial; 20. Apoptosis in the physiology and diseases of the respiratory tract Christian Taube and Martin Schuler; 21. Regulation of cell death in the gastrointestinal track Maria Eugenia Guicciardi and Gregory J. Gores; 22. Apoptosis in the kidney Juan Antonio Moreno, Adrian Mario Ramos, and Alberto Ortiz; 23. Physiological and pathological cell death in the mammary gland Armelle Melet and and Roya Khosravi-Far; 24. Apoptosis in the female reproductive biology - implications for therapy Kaisa Selesniemi and Jonathan L. Tilly; 25. Apoptotic signaling in male germ cells Amiya P. Sinha Hikim, Yue Jia, Yan-He Lue, Christina Wang, and Ronald S. Swerdloff; 26. Cell death in the cardiovascular system Vladimir Kaplinskiy, Martin R. Bennett, and Richard N. Kitsis; 27. Cell death regulation in muscle Ayesha Saleem, Lawrence Kazak, Michael O'Leary, and David A. Hood; 28. Cell death in the skin Saskia Lippens, Esther Hoste, Peter Vandenabeele, and Wim Declercq; 29. Apoptosis and cell survival in the immune system Delphine Me;rino and Philippe Bouillet; 30. Cell death regulations in the hematopoietic system Paul A. Ney; 31. Apoptotic cell death in sepsis Pavan Brahmamdam, Jared T. Muenzer, Richard S. Hotchkiss, and Jonathan E. McDunn; 32. Host-pathogen interactions Maya Saleh; Part III. Cell Death in Non-Mammalian Organisms: 33. Programmed cell death in the yeast, S. cerevisiae Valter D. Longo and Cristina Mazzoni; 34. C. elegans and apoptosis Brian L. Harry and Ding Xue; 35. Apoptoic cell death in drosophila Kathleen Galindo and John M. Abrams; 36. Analysis of cell death in zebrafish Ujwal J. Pyati and A. Thomas Look.
Includes bibliographical references.
Keywords: Apoptosis; Apoptosis -- physiology; Cell death